Regulatory responses to over‐the‐counter codeine analgesic misuse in Australia, New Zealand and the United Kingdom - Claire L. Tobin; Malcolm Dobbin; Brian McAvoy (Australian and New Zealand Journal of Public Health, 2013)
Abstract Objective: Analysis of the policy response by Australia's National Drugs and Poisons Schedule Committee (NDPSC) and comparison with recommendations by expert advisory committees in New Zealand and the United Kingdom. Methods: Analysis of public policy documents of relevant regulatory authorities was conducted. Data were extracted regarding changes to over‐the‐counter (OTC) codeine analgesic scheduling, indications, maximum unit dose, maximum daily dose, maximum pack size, warning labels, consumer medicine information and advertising. Where available, public submissions and other issues considered by the committees and rationale for their recommendations were recorded and thematically analysed. Results: Expert advisory committees in Australia, NZ and the UK defined the policy problem of OTC codeine misuse and harm as small relative to total use and responded by restricting availability. Pharmacist supervision was required at the point‐of‐sale and pack sizes were reduced to short‐term use. Conclusions: Comparison with recommendations by expert advisory committees in NZ and the UK suggests the NDPSC's actions in response to OTC codeine misuse were appropriate given the available evidence of misuse and harm, but highlights opportunities to utilise additional regulatory levers. Implications: Framing policy problems as matters of public health in the context of limited evidence may support decision makers to implement cautionary incremental policy change.